Respuesta :
Assuming linear growth means:
y=mx+b,
m=(y2-y1)/(x2-x1)=(43800-36000)/5
m=1560
y=1560x+b, so y increases by 1560 for every year elapsed...
43800+1560(5)=51600 people five years from now...
Now for the exponential case:
43800/36000=ar^5/ar^0
73/60=r^5
r=(73/60)^(1/5)
43800(73/60)^(1/5)^(5)
43800(73/60)
53290 people five years from now...
y=mx+b,
m=(y2-y1)/(x2-x1)=(43800-36000)/5
m=1560
y=1560x+b, so y increases by 1560 for every year elapsed...
43800+1560(5)=51600 people five years from now...
Now for the exponential case:
43800/36000=ar^5/ar^0
73/60=r^5
r=(73/60)^(1/5)
43800(73/60)^(1/5)^(5)
43800(73/60)
53290 people five years from now...
Answer:
The Correct Answer:
53290 people five years from now
Step-by-step explanation:
Assuming linear growth means:
y=mx+b,
m=(y2-y1)/(x2-x1)=(43800-36000)/5
m=1560
y=1560x+b, so y increases by 1560 for every year elapsed...
43800+1560(5)=51600 people five years from now...
Now for the exponential case:
43800/36000=ar^5/ar^0
73/60=r^5
r=(73/60)^(1/5)
43800(73/60)^(1/5)^(5)
43800(73/60)
Hope I helped you out :)
Comment if you need further help and I'll reply asap :)